Representing the Marginalized Tamang Community in BinaTheeng’s Yaambunera [Near Kathmandu]: A Hallian Analysis - Rai, Jiwan Kumar (Mindscape: A Journal of English & Cultural Studies, 2023)
This paper attempts to analyse Bina Theeng’s “Yaambunera”, the title story of the anthology Yaambunera, exploring the lived experiences of ethnic Taman people of Taulung, an ignored and unheard village, which is an adjoined village of the Kathmandu valley. The paper discusses the lifestyles, socio-economic condition, struggles, hardships and sufferings of the illiterate Tamang community that analyses the literary value and purpose of representing this marginalized world of common Tamang people. Stuart Hall’s concept of representation has been applied as a theoretical tool to achieve the set objectives of the study. Hall argues that representations are not independent and innocent reflections of the real but they are cultural constructions which are selected and constituted by power. In this sense, representation is a cultural product rather than an autonomous process of constructing a meaning. From this theoretical stand, the story is analysed as a discursive representation of Tamang people’s marginalized world that produces and defines the overshadowed body of knowledge about ethnic Tamang community and their ways of life. This study, therefore, provides an insight to see and understand the ways of life and sufferings of poor Tamang people of Taulung, an overlooked village though the village is adjoined to the capital city Kathmandu, Nepal.